Innovation Capabilities and Challenges for Energy Smart Development in Medium Sized European Cities. (June 2016) - Lindhult, Erik; Campillo, Javier; Dahlquist, Erik; Read, Stephen
Abstract: Transition towards becoming Energy smart city integrating different areas of energy production, distribution and use in a community requires a spectrum of capabilities. The paper reports on findings from the EU planning project PLEEC, involving six medium sized European cities. The purpose of the paper is to describe innovation capabilities and challenges in the complex, systemic innovation journey of cities in the transition to sustainability. A case of implementing an innovative project for electrical vehicles in Eskilstuna is presented illustrating both technological potentials and innovation challenges.